Nuevos datos sobre la población y los genoveses en la ciudad de Cádiz. Una relectura del padrón de vecinos de 1467 - Martín Gutiérrez, Emilio (En la España Medieval, 2006)
This study analyzes the size that the population of the city center of Cadiz reached at the moment of its entry into the lordship of the house of Arcos based on the correct edition of the register of neighbours of the city of Cadiz of 1467 and a relation of neighbours of 1468. At the same time, the role of Genoese merchants in the city of Cadiz during that period is examined.